2007
DOI: 10.1074/jbc.m700630200
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Chondroitin Sulfate/Dermatan Sulfate Chains in Brain Development

Abstract: Chondroitin sulfate (CS) and dermatan sulfate (DS) have been implicated in the processes of neural development in the brain. In this study, we characterized developmentally regulated brain CS/DS chains using a single chain antibody, GD3G7, produced by the phage display technique. Evaluation of the specificity of GD3G7 toward various glycosaminoglycan preparations showed that this antibody specifically reacted with squid CS-E (rich in the GlcUA␤1-3GalNAc(4,6-O-sulfate) disaccharide unit E), hagfish CS-H (rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 79 publications
1
33
0
Order By: Relevance
“…The NOP activity of CS/DS chains is mediated by PTN and HGF (19,20), and depends on the presence of disulfated disaccharide units and IdoUA (13)(14)(15)(16)(17)(18)(19)(20). Previously, we isolated sev- (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NOP activity of CS/DS chains is mediated by PTN and HGF (19,20), and depends on the presence of disulfated disaccharide units and IdoUA (13)(14)(15)(16)(17)(18)(19)(20). Previously, we isolated sev- (21).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of oversulfated disaccharides (13)(14)(15)(16) and IdoUA are two crucial factors for these functions of CS/DS chains (19,20), indicating that IdoUA-containing oligosaccharide sequences with specific sulfation patterns may form functional domains for growth factor-binding and NOP activities. However, such functional sequences with a CS/DS hybrid structure are not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because almost no glycosaminoglycans are immunoreactive and there are few antibodies against them, this advantage is extremely useful for generating probes that bind to glycosaminoglycans. Thus, phage display technology is increasingly important for studying the functions of glycosaminoglycans (47)(48)(49)(50)(51)(52). The generation of type-specific anti-HS antibodies using phage display technology was initially applied by van Kuppevelt et al (53) for investigating HS heterogeneity in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) that recognize specific features of the repeating disaccharide region of CS chains have been generated, and epitopes of some of them have been characterized [12][13][14][15][16]. Studies using anti-CS mAbs have revealed restricted spatiotemporal patterns of the expression of specific CS structures in various tissues during growth and development, and in pathological conditions [16][17][18][19]. However, so far, no antibodies have been reported which recognize the GAG-protein linkage region.…”
Section: Introductionmentioning
confidence: 99%